Konstitusionalisasi Hak atas Kebebasan Berekspresi di Era Digital Pasca-Amandemen UUD 1945 - Anastasya; Eny Kusdarini (JURNAL USM LAW REVIEW, 2025)
The disparity between constitutional guarantees and the practice of restricting expression in public and digital spaces reflects a crisis in the effectiveness of human rights protection within the national legal system. Constitutional reform through the Fourteenth Amendment has strengthened the position of the right to freedom of expression, particularly in Article 28E paragraph (3). However, its implementation remains hindered by weak oversight and regulatory ambiguity, especially in Articles 27 and 28 of the Electronic Information and Transactions Law (ITE Law), which are still subject to multiple interpretations. The purpose of this study is to analyze the compatibility between constitutional guarantees of freedom of expression and the practice of legal restrictions in the digital era, based on Lon Fuller’s principle of the internal morality of law. This study is relevant due to the significant gap between constitutional guarantees and the reality on the ground, where restrictions and violations persist, particularly in the digital age. Using a qualitative approach with a normative juridical method, the findings demonstrate that constitutional guarantees are consistent with international standards. Nevertheless, national regulations require adaptive reforms and progressive oversight mechanisms to ensure that freedom of expression can be substantively realized in Indonesia’s constitutional democracy in the digital era. The novelty of this research lies in its critical analysis of Fuller’s internal morality of law, which emphasizes transparency and openness as prerequisites for justice in a democratic legal system, and in its evaluation of the validity of regulations restricting freedom of expression in Indonesia’s digital age.   Ketimpangan antara jaminan konstitusional dan praktik pembatasan ekspresi di ruang publik dan digital menunjukkan adanya krisis efektivitas perlindungan hak asasi manusia dalam sistem hukum nasional. Reformasi konstitusi melalui empat kali amandemen memang telah memperkuat posisi hak berekspresi, khususnya dalam Pasal 28E ayat (3), namun penerapannya masih terkendala lemahnya pengawasan, ambiguitas regulasi terutama Pasal 27 dan 28 UU ITE yang masih multitafsir. Tujuan  penelitian ini adalah menganalisis kesesuaian antara jaminan konstitusional kebebasan berekpresi dan praktik pembatasan hukum di era digital berdasarkan prinsip moralitas internal hukum Lon Fuller. Penelitian ini relevan karena adanya kesenjangan antara jaminan konstitusi yang baik dengan realitas di lapangan yang masih banyak pembatasan dan pelanggaran, terutama di era digital. Penelitian ini menggunakan pendekatan kualitatif dengan jenis yuridis normatif. Hasil penelitian menunjukkan bahwa jaminan konstitusional telah selaras dengan standar internasional, tetapi regulasi nasional masih membutuhkan pembaruan adaptif dan mekanisme pengawasan yang progresif agar kebebasan berekspresi dapat terwujud secara substantif di era digital dan demokrasi konstitusional Indonesia. Kebaruan penelitian terletak pada analisis kritis terhadap moralitas internal hukum menurut Fuller, yang menekankan pentingnya transparansi dan keterbukaan sebagai prasyarat keadilan dalam sistem hukum demokratis dan menilai keabsahan regulasi pembatasan kebebasan berekspresi di era digital Indonesia.